Life Cycle of the Lesser Cornstalk Borer in Sugarcane - Hardev S. Sandhu; Leslie E. Baucum; Gregg S. Nuessly (EDIS)
The lesser cornstalk borer attacks a large number of crops but is a potentially serious pest of sugarcane. But since the populations of this pest vary greatly depending on temperature, UF/IFAS scientists are developing predictive models to predict lesser cornstalk borer population in a field. This 4-page fact sheet was written by H.S. Sandhu, L.E. Baucum, and G.S. Nuessly and published by the UF Department of Entomology and Nematology, September 2011.